An interwar family as portrayed by “Dom Rodzinny” (1925–1933) - Michalska, Iwonna (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The purpose of the work is to reconstruct the message sent by the editors of the “Dom Rodzinny” („Family Home”) weekly, a supplement to the “Słowo Pomorskie” (“Word of Pomerania”) daily published in Toruń since 1921, which described “model lives” of Catholic families. The research was conducted using the method of contents analysis. Results. The results of the research which included nine annual volumes of the magazine led to the conclusion that the areas which a particular attention was paid to included strengthening faith and providing information on religious and church issues, building patriotic attitudes by reminding the complex history of Poland, national heroes, and great Poles, defining the role of women at home and in society, making readers sensitive to care in bringing up children, and building relationships between family members and friends. Furthermore, the magazine’s aspiration was to prevent modern Catholic families from losing touch with the surrounding reality and various new tendencies and novelties. The magazine’s authors were open to the world and propagated the idea of sightseeing, encouraged the readers to study exotic cultures, disseminated readership, informed the readers on technical news, and even provided discreet tips on selecting comfortable, practical, cheap, and fashionable clothes for parents and children.
Keywords: catholic family; catholic magazines; “Dom Rodzinny” periodical; interwar period